Where and why to conserve grasslands socio-ecosystems? A spatially explicit participative approach - Staiano, Luciana (2022)
Grasslands of southern South America are being replaced by annual crops and forest plantations. The environmental and social consequences of this expansion generate the need for its regulation. If a conservation policy were established, it would be critical to define which areas would have priority for conservation. Multi-criteria analysis techniques are useful tools in territorial planning processes since they allow incorporating diverse and even opposing opinions and objectives. We present a methodological approach to define the Grasslands’ Conservation Value (GCV) from a spatially explicit territorial diagnosis, based on multiple criteria and incorporating explicitly and quantitatively the valuations and opinions of stakeholders. The study was developed as part of the strategy of a public inter-institutional entity to contribute in defining grasslands conservation policies. The methodological approach included workshops in which the definitions of the conservation criteria and their weighting were agreed upon. Definitions were based on a multidimensional technical characterization of the territory through indicators, for which the information used was compiled, analyzed, shared, and synthesized. Based on multi-criteria analysis, each of 12 stakeholders’ groups representatives established the individual weighting of the criteria for determining the GCV and then, established a consensus weighting. The GCV was mapped by integrating territorial diagnosis of these criteria with the weightings carried out by the stakeholders. The degree of agreement among stakeholders in the differential valuation of the ecological criteria was high for 8 of the 12 stakeholders (Pearson’s correlation coefficients >0.92), showing a high agreement between their opinions and those resulting from the group consensus. In all cases, the agreement about the spatial variation of conservation value was higher than on the criteria weights (Pearson’s correlation coefficients ≥0.92 for 10 stakeholders). Furthermore, the sites with lower values in the consensus map corresponded mostly to those sites with lower agreement among stakeholders. The proposed methodology allowed the incorporation of different perceptions not only in the definition of conservation criteria but also in their prioritization, in a transparent and auditable process. This could contribute to the implementation of future regulations that restrict the replacement of grasslands, increasing the legitimacy of territorial planning processes.